Breaking free from death : the art of being a successful Russian writer - Rylkova, Galina (Academic Studies Press, 2020)
"Breaking Free from Death examines how Russian writers respond to the burden of living with anxieties about their creative outputs, and, ultimately, about their own inevitable finitude. What contributes to creative death are not just crippling diseases that make man defenseless in the face of death, and not just the arguably universal fear of death but, equally important, the innumerable impositions on the part of various outsiders. Many conflicts in the lives of Rylkova's subjects arose not from their opposition to the existing political regimes but from their interactions with like-minded and supporting intellectuals, friends, and relatives. The book describes the lives and choices that concrete individuals and-by extrapolation-their literary characters must face in order to preserve their singularity and integrity while attempting to achieve fame, greatness, and success"--